Ontology and the semantic web - Colomb, Robert M. (IOS Press, 2013)
Nearly every business or organization is supported by an information system. Companies in the finance, insurance and real estate industry group are very little more than information systems. Mines and farms use information systems to keep track of production and assets. Manufacturers, wholesalers and retailers use information systems to manage their production, sales and employees. Construction firms use information systems to bid for and manage projects. Transportation firms use them to schedule services. The health sector is served by thousands of systems assisting in the operation of various departments in hospitals, doctors’ surgeries, and the flow of payments through the system. Universities use information systems to keep track of students, courses, libraries and staff. Governments use them to record births, deaths and marriages, and in the provision of all sorts of services.